PENGARUH CHATBOT AI TERHADAP HASIL BELAJAR DI SMK - Yolanda Tamara; Budi Syahri; Refdinal Refdinal; Mulianti Mulianti (Unversitas Negeri Padang, 2024)
The aim of this study is to explore the relationship between the use of AI chatbots and learning outcomes in the field of basic mechanical engineering among students of SMK Negeri 1 Lintau Buo. Although conventional teaching methods are used, this study is considered necessary due to the insufficient learning performance of the students in meeting the minimum completion criteria. The research method used in this study is quasi-experimental, this is a form of quantitative research. The participants were 59 students of class X of the mechanical engineering program. The analysis of the data showed that both the data come from populations with normal distribution and homogeneity. This has been confirmed by Liliefors and Fisher normality tests. Due to the fact that the calculated t-value of 2.341 exceeded the decisive t-value of 2.002, the results demonstrated the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1) at a significance level of 0.05. This was evidenced by a substantial improvement in the average pupils in the experimental group's post-test results, rising from an initial average score of 66.2 to 83.58 after the implementation of the AI chatbot as an educational support platform.